Adult-Onset Solitary Verrucous Epidermal Nevus Without Blaschkoid Distribution: A Clinicopathological Diagnostic Challenge - Sekar Sari Arum Palupi; Chintya Nur Fa’izah; Haken Tennizar Toena; Putri Atthariq Ilmi (Jurnal Kesehatan dan Kedokteran, 2026)
Verrucous epidermal nevus (VEN) is a benign keratinocytic hamartoma that usually appears in childhood and follows Blaschko’s lines. Adult-onset solitary VEN without Blaschko line distribution is rare and may clinically mimic other verrucous lesions, including verruca vulgaris, seborrheic keratosis, and verrucous squamous cell carcinoma. Objective: This case report aims to describe an atypical adult-onset solitary VEN without Blaschko line distribution and emphasize the importance of clinicopathological correlation in establishing the diagnosis. Case: A 27-year-old man presented with a progressively enlarging verrucous plaque on the left lateral malleolus for one year. The lesion was hyperkeratotic, well-demarcated, and associated with pruritus. Clinical differential diagnoses included verruca vulgaris, seborrheic keratosis, and verrucous squamous cell carcinoma. Complete surgical excision was performed, followed by histopathological examination. Discussion: Histopathological findings showed hyperkeratosis, papillomatosis, focal hypergranulosis, acanthosis, and basal hyperpigmentation without koilocytosis, horn cysts, cytologic atypia, or invasive growth. These findings confirmed the diagnosis of VEN and excluded infectious and malignant verrucous lesions. Conclusion: Solitary adult-onset VEN without Blaschko line distribution is a rare diagnostic challenge. Histopathological examination is essential for accurate diagnosis, while excisional biopsy may serve both diagnostic and therapeutic purposes in localized lesions.